Glycated Albumin and Risk of Mortality in the US Adult Population. (29th January 2022) - Rooney, Mary R; Daya, Natalie; Tang, Olive; McEvoy, John William; Coresh, Josef; Christenson, Robert H; Selvin, Elizabeth
Abstract: Background: Glycated albumin is of growing interest as an alternative biomarker of glycemia. However, the association of glycated albumin with long-term outcomes in the general population is uncharacterized. We evaluated the associations of glycated albumin and hemoglobin A1c (HbA1c) with mortality in US adults. Methods: We conducted a prospective analysis of 12 915 participants in the National Health and Nutrition Examination Survey 1999–2004. We used Cox regression to characterize associations of glycated albumin and HbA1c with all-cause and cardiovascular mortality through 2014. We categorized glycated albumin based on percentiles corresponding to clinical cut-points for HbA1c. No diagnosed diabetes: <5.0% (<12th percentile), 5.0% to 5.6% (12th–82nd percentile, reference), 5.7% to 6.4% (83rd–97th percentile), and ≥6.5% (≥98th percentile). Diagnosed diabetes: <7.0% (<50th percentile), 7.0% to 8.9% (50th–83rd percentile), and ≥9.0% (≥84th percentile). Results: Among US adults (mean age 46 years), the prevalence of diagnosed diabetes was 6.8%. Glycated albumin and HbA1c were highly correlated ( r = 0.76). Over the median 16.8 years follow-up, there were 2818 deaths (652 cardiovascular). Adults with diagnosed diabetes and glycated albumin ≥84th percentile had the highest risk for all-cause mortality [hazard ratio (HR) 3.96, 95% CI 3.06–5.13] and cardiovascular mortality (HR 6.80, 95% CI 4.20–11.03). HbA1c had associations with all-cause and cardiovascular mortality that were similar to those for glycated albumin. Conclusions: Among US adults, increased values of glycated albumin and HbA1c were associated with all-cause and cardiovascular mortality, particularly in persons with diagnosed diabetes. Glycated albumin may be a useful alternative test of glycemia.